1993
DOI: 10.1177/002221949302600103
|View full text |Cite
|
Sign up to set email alerts
|

Learning, School Performance, and Children with Asthma

Abstract: Children with asthma may be at risk for decreased school functioning due to acute exacerbations, increased absenteeism, iatrogenic effects of their asthma medication, and the stress associated with a chronic illness. The purpose of this article is to critically review extant research pertaining to the school functioning of children with asthma, including studies of school attendance, school performance, the effects of asthma medications on learning and behavior, and the role of psychological variables in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…This imposes significant restrictions on physical activities and can affect school attendance [2][3][4] and performance [5]. Night-time awakenings and poor disease control [6] result in reduced perceptions of self-esteem and increased behaviour problems [7][8][9]. Despite this, evidence suggests that teacher knowledge and training in asthma management is low, asthma records are incomplete, and effective child self-management of inhaler therapy is unsatisfactory [3,[10][11][12].…”
mentioning
confidence: 99%
“…This imposes significant restrictions on physical activities and can affect school attendance [2][3][4] and performance [5]. Night-time awakenings and poor disease control [6] result in reduced perceptions of self-esteem and increased behaviour problems [7][8][9]. Despite this, evidence suggests that teacher knowledge and training in asthma management is low, asthma records are incomplete, and effective child self-management of inhaler therapy is unsatisfactory [3,[10][11][12].…”
mentioning
confidence: 99%
“…• (Aronson, 1995;Celano & Geller, 1993;Getch & Neuharth-Pritchett, 1999;Schwartz, 1999;Simeonsson et al, 1995) Increasing hospitalization and mortality rates are being reported among children with this condition ( da Costa, Rapoff, Lemanek, & Goldstein, 1997), with symptoms of varying severity. When individuals experience a severe attack, talking and breathing can become difficult (American Lung Association [ALA], 2002a; The Lung Association, n.d.).…”
Section: Asthmamentioning
confidence: 99%
“…Asthma attacks may have to be treated with rest, medications, reductions and restrictions in physical activities, and a trip to a doctor or hospital may be required (Aronson, 1995;Celano & Geller, 1993;Getch & Neuharth-Pritchett, 1999;Simeonsson et al, 1995). A variety of both long-term and short-term control medications are available for individuals with asthma, including inhaled, liquid, and oral medications.…”
Section: Medical Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…56 Even short absences from school can influence academic performance in later life. 57 Although teachers generally have accepting attitudes towards asthma, their knowledge about asthma is low and they are not adequately prepared to assist children with the management of asthma in the classroom.…”
Section: School Performancementioning
confidence: 99%